Adaptive Communication Strategies for Drug Prevention: A Netnographic Analysis of the Surabaya BNN’s Instagram Account - Sherly Amelia Nur Faizzah; Citra Rani Angga Riswari; Farida (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study analyzes the communication strategy of the National Narcotics Agency (BNN) of Surabaya City in utilizing Instagram (@infobnn_kota_surabaya) for drug prevention education. Contributing a culturally adaptive framework, the research employs a qualitative netnography method to examine Anwar Arifin’s four communication strategy concepts. The sample encompasses all agency Instagram posts observed from January to March 2026. Results indicate BNN effectively applies these stages by targeting urban youth, constructing AI-supported messages, implementing canalizing methods through local mascots (Cula-Baya) and jargon, and maximizing Instagram's ecosystem. Ultimately, this culturally relevant digital strategy amplifies cyber-based prevention programs, providing a replicable communication model for other public institutions.